Gender maturation development in childhood: a theoretical systematization of international manuals on human development (Research, Society and Development, 2022)
This research has as its general objective: to systematize the content on gender development in childhood present in international human development manuals. It is an exploratory bibliographic (state of the art) study with a qualitative approach. The materials used were international human development manuals that address the theme of gender development in childhood. In these manuals, theories of gender development appear with different nomenclatures, however, it was possible to identify eleven theories that deal with the researched theme. Among the findings of this research, it was observed that: all the manuals found are of American origin; the manuals present a great diversity of theory about gender development; some of these theories appear more than others in the referred manuals; the theories present approximations and distances in terms of their foundations.